Estratégias alimentares para recria de cordeiras em pastagem de milheto - Jochims, Felipe (2008)
The experiment was conducted in the Department of animal science, of the Universidade Federal de Santa Maria, to value a feed strategy for Texel x Ile de France crossbred ewe lambs rearing by animal performance and feeding behavior. All the animals were allocated in a pasture of Pearl millet (Pennisetum americanum (L) Leeke), under continuous variable stocking. The treatments were: corn gluten meal; cassava meal; non supplemented animals. The supplementation were fed at 1% of live weight. It was evaluated weaned ewe lambs. The experimental design was completely randomized with repeated measures in time with tree treatments and two area replicates. The tratament of the corn gluten meal results a bigger average daily gain (P<0,05) and a higher area gain (P=0,06). The supplement supply to the ewe lambs influenced the grazing time bite size and bite rate. Animal of the all treatments reached 60% of your adult live weight.